Application of Physics Learning Based on Pacu Jalur Tradition to Improve Cognitive Abilities Students of SMA - Amelia Syafitri; Z. Zulirfan; Zuhdi Maaruf (Science Education Department of Mathematics and Natural Sciences Education Faculty of Teacher Training and Education, Universitas Riau in collaboration with the Association of Indonesian Science Educators (PPII), 2024)
The purpose of this research was to determine the effect of ethnoscience-based learning methods of Pacu Jalur Tradition on the cognitive abilities of class XI students of SMA Negeri 1 Kuantan Hilir. The methodology used in this research is quasi-experiment with a non-equivalent post-test design. Samples were analyzed randomly after normality and homogeneity tests were completed to determine the experimental group and control group. This research used test instruments in the form of multiple-choice questions about cognitive abilities. Analysis of research data using Microsoft Excel and SPSS. The results of the independent sample t-test hypothesis test on cognitive abilities are shown with a significance level of 0.002 ≤ 0.05. There is a significant difference in students' cognitive abilities between ethnoscience-based learning in the Pacu Jalur Tradition and conventional classes. Learning based on the Pacu Jalur Tradition is effective in improving the cognitive abilities of students at SMA Negeri 1 Kuantan Hilir on the kinematics of straight motion.